3D digital outcrop model reconstruction of the Kimberley outcrop (Gale crater, Mars) and its integration into Virtual Reality for simulated geological analysis. (March 2020) - Caravaca, Gwénaël; Le Mouélic, Stéphane; Mangold, Nicolas; L'Haridon, Jonas; Le Deit, Laetitia; Massé, Marion
Abstract: Structure-from-Motion photogrammetry has recently become a cheap and efficient method to reconstruct accurate and highly-resolved 3D Digital Outcrop Model (DOM) from a single set of images. This enables the 3D visualization of hardly accessible and/or remote geological scenes, which is of strong interest for planetary bodies. This paper focuses on the reconstruction of the DOM of the Kimberley outcrop (Gale crater, Mars) using the Agisoft PhotoScan Professional software. This software is used to compute an accurate, scaled and georeferenced 3D mesh of this outcrop from set of multi-scale images taken by the Mars Science Laboratory rover Curiosity . This model was merged with a 3D model computed from orbital images from the High Resolution Imaging Science Experiment camera (HiRISE) to provide the context. One of the challenges is to integrate data coming from different cameras (with varying optical parameters) not specifically designed for 3D rendering, and with limited points of views. While the obtained DOM allows to observe and characterize geological features of Kimberley's sedimentary series, classic viewing methods through a 2D screen limits the understanding of the real 3D geometry and scale of the outcrop, as there is no feature such as trees or roads on Mars to provide size references to the user. To overcome this issue and facilitate the interpretation of the DOM, the latter is integrated into a Virtual Reality (VR) environment that enables one or several users working in a collaborative mode to experience a real scale, reliable and realistic depiction of the actual geometries of the geological features reconstructed on the mesh. Precise and accurate description, contextualization of the samplings and mapping of the Kimberley outcrop can therefore be achieved in VR allowing for more precise characterization and interpretations, the same way one would do on a real geological field trip. Highlights: Digital Outcrop Modeling of a Curiosity rover field site on Mars. Integration into Virtual Reality for real scale visualization of the features. VR-enabled geological analysis of the accurately reconstructed Martian outcrop. VR allows for characterization of previously underrated sedimentological features.